1003. OROBANCHE RAPUM‐GENISTAE: Orobanchaceae. (9th November 2021) - J. Thorogood, Chris; J. Rumsey, Fred
Summary: The distribution, ecology and taxonomic history of Orobanche rapum‐genistae Thuill. are discussed with particular reference to the British Isles and elsewhere in Europe where the plant has retracted markedly within its former range. The variation present within the species is described and the typical form is illustrated. The outlook for this sharply declining species is considered in the broader context of parasitic plant ecology and conservation.